Acute post-exercise change in blood pressure and exercise training response in patients with coronary artery disease - Kiviniemi, Antti M.; Hautala, Arto J.; Karjalainen, Jaana J.; Piira, Olli-Pekka; Lepojärvi, Samuli; Ukkola, Olavi; Huikuri, Heikki V.; Tulppo, Mikko P. (Frontiers in Physiology, 2015)
We tested the hypothesis that acute post-exercise change in blood pressure (BP) may predict exercise training responses in BP in patients with coronary artery disease (CAD). Patients with CAD (n=116, age 62±5 years, 85 men) underwent BP assessments at rest and during 10-min recovery following a symptom-limited exercise test before and after the 6-month training intervention (one strength and 3-4 aerobic moderate-intensity exercises weekly). Post-exercise change in systolic BP (SBP) was calculated by subtracting resting SBP from lowest post-exercise SBP. The training-induced change in resting SBP was -2±13 mmHg (p=0.064), ranging from -42 to 35 mmHg. Larger post-exercise decrease in SBP and baseline resting SBP predicted a larger training-induced decrement in SBP (β=0.46 and β=-0.44, respectively, p<0.001 for both). Acute post-exercise decrease in SBP provided additive value to baseline resting SBP in the prediction of training-induced change in resting SBP (R squared from 0.20 to 0.26, p=0.002). After further adjustments for other potential confounders (sex, age, baseline body mass index, realized training load), post-exercise decrease in SBP still predicted the training response in resting SBP (β=0.26, p=0.015). Acute post-exercise change in SBP was associated with training-induced change in resting SBP in patients with CAD, providing significant predictive information beyond baseline resting SBP.